Умови формування вокальних навичок у старших дошкільників на основі традицій української співацької культури - Кузьменко, Альона Анатоліївна (My University, 2022)
Наукова робота присвячена аналізу проблеми формування у дітей старшого дошкільного віку співацьких навичок. Здійснено аналіз наукових підходів до проблеми формування вокальних навичок у дітей 6-7 років життя. Визначено специфіку навчання старших дошкільників співу на заняттях з музичного виховання у ЗДО. Надано соціокультурну та педагогічну характеристику традицій української співацької культури. Визначено ряд традицій, які можливо використовувати в сучасній музично-виховній практиці закладу дошкільної освіти. Розроблено критерії, показники та виявлено у процедурі констатувального експерименту рівні сформованості співацьких навичок у старших дошкільників. Виявлено чинники впливу на ефективність співацької роботи з дітьми у ЗДО. Запропоновано програму експериментальної роботи щодо використання традицій української співацької культури у навчанні співу дітей старшого дошкільного віку.
Kuzmenko A. A. Conditions for the formation of vocal skills in senior preschool children based on the traditions of Ukrainian spivatskoi Kultury / A. A. Kuzmenko. - Qualification work. Nizhin, 2022, p. 91 р. (in Ukrainian). The scientific work is devoted to the analysis of the problem of formation of singing skills in older preschool children. The analysis of scientific approaches to the problem of formation of vocal skills in children aged 6-7 years of life is carried out. The specifics of teaching older preschoolers to sing in music education classes in ZDO are determined. Socio-cultural and pedagogical characteristics of the traditions of Ukrainian singing culture are given. A number of traditions that can be used in the modern musical and educational practice of preschool education institutions are identified. Criteria and indicators are developed and the level of formation of vocal skills in older preschoolers is revealed in the procedure of the ascertaining experiment. Factors influencing the effectiveness of vocal work with children are identified in ZDO. A program of experimental work on the use of traditions of Ukrainian singing culture in teaching singing to older preschool children is proposed. Keywords: singing, singing training, singing skills, musical education of preschool children, tradition, singing culture, traditions of Ukrainian singing culture.
Keywords: музичне виховання дошкільників; традиції української співацької культури